Enhancing the content- and language-integrated multiple literacies framework: Systemic functional linguistics for teaching regional diversity. (February 2021) - Ryshina-Pankova, Marianna; Barthold, Willi; Barthold, Emily
Abstract: While content- and language-integrated instruction has been considered crucial for the development of literacy in a foreign language (FL) (e.g., Cammarata, Tedick, & Osborne, 2016), implementing an integrated approach is often challenging. This article demonstrates how systemic functional theory (SFL) (Halliday & Matthiessen, 2014) that establishes explicit connections between the linguistic and the social can be instrumental for integrated pedagogy design that promotes a critical orientation to text. Responding to the need to diversify content typically taught in German curricula, the article shows how instructors can expose learners to the multifaceted nature of the German cultural cosmos by focusing on two regions through Sorbian and Mecklenburg tales. Enhancing the pedagogy of multiliteracies (The New London Group, 1996), the article presents SFL-based concepts as tools for textual analysis and content- and language-integrated exploration of the texts. We demonstrate how instructional tasks based on the SFL analysis provide learners with a critical lens to examine how variation in the narrative structure and patterns of language use construe particular aspects of regional cultures and point to conceptualizations of human-nature relationships and gender roles that differ from traditional fairytales. In doing so, genre-based tasks help learners reflect on cultural representations and creatively apply linguistic and content knowledge.